Key points to design a training plan for the Education Inspectorate in Spain - Rodríguez Bravo, Marcos Francisco; Álvarez, Carmen Álvarez; Camacho Prats, Alexandre (Avances en Supervisión Educativa, 2018)
Today, education inspectors require more general training and specialization in order to adequately carry out their positions. The quality in training of inspectors in Spain has fundamentally fallen in public administrations and this, in the context of the different Spanish regions, has contributed to different results without a determined standard. In order to better understand this problem and elaborate on the present article, we have analyzed all the current regional regulations related to the organization and operation of the Education Inspector services. At the root of this analysis, we conclude with a series of key proposals that allow the public administrations to design up to date permanent training plans, which are relevant and effective for the Inspectors.